Handheld reflectance confocal microscopy: Personalized and accurate presurgical delineation of lentigo maligna (melanoma). Issue 3 (24th November 2020) - Elshot, Yannick S.; Zupan‐Kajcovski, Biljana; Klop, William M. C.; Bekkenk, Marcel W.; Crijns, Marianne B.; de Rie, Menno A.; Balm, Alfons J. M.
Abstract: Background: The surgical treatment of lentigo maligna melanoma is associated with high rates of local recurrence. Handheld reflectance confocal microscopy (HH‐RCM) allows for in vivo presurgical detection of subclinical lentigo maligna (melanoma) (LM/LMM). Methods: A single‐center retrospective study from December 2015 to July 2017. Frequency and extent of negative surgical margins, and the diagnostic accuracy of presurgical mapping by HH‐RCM was determined. Results: Twenty‐six consecutive patients with LM/LMM were included. In 45.8%, HH‐RCM detected subclinical LM with a sensitivity of 0.90 and specificity of 0.86. The management was changed in two (7.7%) patients. Of the 24 remaining lesions, 95.8% were excised with negative margins with a mean histological margin of 3.1 and 5.3 mm for LM and LMM, respectively. At a mean follow‐up of 36.7 months, there was one (4.8%) confirmed recurrence. Conclusions: Our method of presurgical delineation by HH‐RCM appears to provide a reliable method for the surgical treatment of LM/LMM with a limited rate of overtreatment.